2008
DOI: 10.1038/ng.223
|View full text |Cite
|
Sign up to set email alerts
|

Insights from retinitis pigmentosa into the roles of isocitrate dehydrogenases in the Krebs cycle

Abstract: We describe two families with retinitis pigmentosa (RP), a hereditary neurodegeneration of rod and cone photoreceptors in the retina, in which affected members were homozygotes for loss-of-function mutations in the IDH3B gene encoding the beta subunit of NAD-specific isocitrate dehydrogenase (NAD-IDH), the enzyme believed to catalyze the oxidation of isocitrate to α-ketoglutarate in the citric acid cycle. Cells from the affected family members had a substantial reduction of NAD-IDH activity with about a 300-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(133 citation statements)
references
References 20 publications
5
124
0
Order By: Relevance
“…Homozygous loss-of-function mutations in IDH3B have been found in two families with retinitis pigmentosa (49), and somatic mutations in IDH3B have been recently found in acute myelogenous leukemia (50). IDH3B encodes the beta subunit of NADspecific isocitrate dehydrogenase 3 (IDH3), which is involved in the oxidation of isocitrate to a-ketoglutarate in the Krebs cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homozygous loss-of-function mutations in IDH3B have been found in two families with retinitis pigmentosa (49), and somatic mutations in IDH3B have been recently found in acute myelogenous leukemia (50). IDH3B encodes the beta subunit of NADspecific isocitrate dehydrogenase 3 (IDH3), which is involved in the oxidation of isocitrate to a-ketoglutarate in the Krebs cycle.…”
Section: Discussionmentioning
confidence: 99%
“…IDH3B encodes the beta subunit of NADspecific isocitrate dehydrogenase 3 (IDH3), which is involved in the oxidation of isocitrate to a-ketoglutarate in the Krebs cycle. It has been demonstrated that IDH3 activity in lysates from cells carrying heterozygous truncating IDH3B mutations was only 24% of that observed in normal controls (49). In addition, the altered a-ketoglutarate/isocitrate ratio detected in the tumor carrying the truncating mutation, and the associated CIMP-like profile further suggest a causative role for this variant in PGL development.…”
Section: Discussionmentioning
confidence: 99%
“…Isocitrate dehydrogenase 3 and IMP dehydrogenase have central roles in mitochondrial and purine metabolism, but mutations in these widely expressed genes do not cause degeneration outside the retina. However, mutations in isocitrate dehydrogenase 3 (65) and IMP dehydrogenase (66) do cause photoreceptors to degenerate. The preponderance of aerobic glycolysis in retina, the light-sensitive activity of mitochondria, and the light sensitivity of nucleotide metabolism may be key for understanding why retinas are uniquely sensitive to these mutations.…”
Section: Significance For Retinal Diseasementioning
confidence: 99%
“…From a functional viewpoint, both branches of the TCA cycle seem to be "short-circuited" in the nucleus by the absence of a few critical proteins (the pathway involving IDH2 is thought to be a minor contributor 61 ) again suggesting that these proteins have different roles in the nucleus and in mitochondria. Furthermore, if PC/PDPR (6/2 peptides and 6/2 counts in the nucleus respectively, Supporting Information Table 2) are not present or strongly reduced in the mitochondria of MCF7 cells, this would be expected to have major effects on the metabolic flux of pyruvate through acetyl-CoA, oxaloacetate or lactate ( Figure 3).…”
Section: Partitioning Of Tri-carboxylic-acid Cycle Proteinsmentioning
confidence: 99%